2018
DOI: 10.1093/ehjci/jey011
|View full text |Cite
|
Sign up to set email alerts
|

Overview of mitral regurgitation in Europe: results from the European Registry of mitral regurgitation (EuMiClip)

Abstract: To date, this is the largest echocardiography-based study to analyse the prevalence and aetiology distribution of MR in Europe. The burden of secondary MR was higher than previously described, representing 30% of patients with significant MR. In our environment, degenerative disease is the most common aetiology of primary MR (60%), whereas ischaemic is the most common aetiology of secondary MR (51%). Up to 70% of patients with severe primary MR may have a Class I indication for surgery. However, the optimal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 14 publications
0
21
0
1
Order By: Relevance
“…Studies from Southwest Ethiopia, 12 Madrid, Spain, 22 and 19 European centers 23 revealed that RHD was significantly higher in females when compared to males. Similarly, the current study indicated a high rate of RHD among females (35%) when compared to males (16.4%).…”
Section: Discussionmentioning
confidence: 98%
“…Studies from Southwest Ethiopia, 12 Madrid, Spain, 22 and 19 European centers 23 revealed that RHD was significantly higher in females when compared to males. Similarly, the current study indicated a high rate of RHD among females (35%) when compared to males (16.4%).…”
Section: Discussionmentioning
confidence: 98%
“…This ratio is in agreement with a recent prospective multicentre echocardiographic registry. 31 Therapeutic approaches for SMR remain a matter of debate and the benefit of surgical correction of SMR is disputed. 13 32 33 Interestingly and despite these uncertainties, half of the patients with SMR underwent an isolated MV surgery, a markedly higher rate than one might have expected.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, progressive sMR occurs in 20%‐30% of patients with nonsevere sMR despite GDT and is independently associated with a more than twofold increased risk of death . Defining patients at risk for progression is mandatory as in this patient subpopulation more invasive early treatment strategies are available but the level of evidence in guideline recommendations is weak . Whilst it has been shown that invasive treatment for sMR can delay or even prevent progressive HF, characteristics of patients that may benefit most and the optimal time‐point for intervention are not ultimately determined .…”
Section: Discussionmentioning
confidence: 99%